Incidental findings of elevated random plasma glucose in the ED as a prompt for outpatient diabetes screening: a retrospective study. Issue 12 (18th December 2013) - Friedman, Steven Marc; Vallipuram, Janaki; Baswick, Brenda
Abstract : Objective: To determine whether random plasma glucose (RPG) collected from patients without known impaired glucose metabolism (IGM) in the emergency department (ED) is a useful screen for diabetes or prediabetes. Design: Retrospective cohort study. Setting: ED of a Canadian teaching hospital over 1 month. Participants: Adult patients in ED with RPG over 7 mmol/L were recruited for participation. Exclusion criteria included known diabetes, hospital admission and inability to consent. Participants were contacted by mail, encouraged to follow-up with their family physician (FP) for further testing and subsequently interviewed. Outcome measures: The primary outcome measure was the proportion of patients in the ED with RPG over 7 mmol/L and no previous diagnosis of IGM who were diagnosed with diabetes or prediabetes after secondary testing by FP with oral glucose tolerance test or fasting plasma glucose (FPG). Secondary outcomes included patient characteristics (age, gender, body mass index and language) and (2) compliance with advice to seek an appropriate follow-up care. Results: RPG was drawn on approximately one-third (33%, n=1149) of the 3470 patients in the ED in March 2010. RPG over 7 mmol/L was detected in 24% (n=278) of patients, and after first telephone follow-up, 32% (n=88/278) met the inclusion criteria and were advised to seek confirmatory testing. 41% (n=114/278) of patients were excluded for known diabetes. 73% of patients contacted (n=64/88) followed up with their FP. 12.5% (n=11/88) of patients had abnormal FPG, and of these 11% (n=10/88) were encouraged to initiate lifestyle modifications and 1% (n=1/88) was started on an oral hypoglycaemic agent. For 7% (n=6/88) of patients, FP's declined to do follow-up fasting blood work. Conclusions: Elevated RPG in the ED is useful for identification of patients at risk for IGM and in need of further diabetic screening. Emergency physicians should advise patients with elevated RPG to consider screening for diabetes. For ED screening to be successful, patient education and collaboration with FPs are essential.